2012
DOI: 10.1182/blood-2011-10-381715
|View full text |Cite
|
Sign up to set email alerts
|

Model systems of genetically modified platelets

Abstract: Although platelets are the smallest cells in the blood, they are implied in various processes ranging from immunology and oncology to thrombosis and hemostasis. Many large-scale screening programs, genome-wide association, and "omics" studies have generated lists of genes and loci that are probably involved in the formation or physiology of platelets under normal and pathologic conditions. This creates an increasing demand for new and improved model systems that allow functional assessment of the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 141 publications
(100 reference statements)
1
17
0
Order By: Relevance
“…Pertuy et al found that 0.3% of CD45 + leukocytes as well as a small percentage of intestinal epithelial cells showed expression of Pf4. Despite these results, the authors confirmed that the Pf4-Cre system is extremely valuable and a powerful instrument to study the function of megakaryocytes and platelets in diverse physiological and pathological settings, as also shown by others (58 with regard to tumor growth and tumor rebound after withdrawal of antiangiogenic therapy were found using the FAK inhibitor GSK2256098, which combined well when given together with the antiangiogenic agents pazopanib or bevacizumab. GSK2256098 is a highly specific small-molecule inhibitor for FAK, both for humans and mice, and has been designed to block FAK Y397 phosphorylation which is necessary for kinase activation (59).…”
Section: Discussionmentioning
confidence: 78%
“…Pertuy et al found that 0.3% of CD45 + leukocytes as well as a small percentage of intestinal epithelial cells showed expression of Pf4. Despite these results, the authors confirmed that the Pf4-Cre system is extremely valuable and a powerful instrument to study the function of megakaryocytes and platelets in diverse physiological and pathological settings, as also shown by others (58 with regard to tumor growth and tumor rebound after withdrawal of antiangiogenic therapy were found using the FAK inhibitor GSK2256098, which combined well when given together with the antiangiogenic agents pazopanib or bevacizumab. GSK2256098 is a highly specific small-molecule inhibitor for FAK, both for humans and mice, and has been designed to block FAK Y397 phosphorylation which is necessary for kinase activation (59).…”
Section: Discussionmentioning
confidence: 78%
“…1 Defects in platelet number or function often result in primary hemostatic disorders or thrombotic events such as myocardial infarction and stroke. 2,3 A significant body of research has been dedicated to the identification of proteins that regulate platelet number and function with the goal of developing therapies for affected individuals. Through genome-wide association and proteomic studies, a number of genes have been recognized to play a role in platelet activity.…”
mentioning
confidence: 99%
“…3,8,9 ). Unlike mammals, zebrafish thrombocytes are nucleated, but they share structural and functional features with platelets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[138][139][140][141][142] Not only are these zebrafish genes syntenic to human genes, functional assays have also shown that extrinsic and intrinsic coagulation factors and several platelet surface receptors are also present in zebrafish blood or thrombocytes. 143,144 Zebrafish have nucleated thrombocytes which are functionally equivalent to enucleated platelets in mammals. 145 Similarly, the vascular endothelium in zebrafish possesses several factors found in human endothelial cells.…”
Section: Modeling Thrombosis and Hemostasis In Zebrafishmentioning
confidence: 99%